Suggested policies in regard to suburban expansion into the urban fringe : using the Constantia Valley as a case study - Callaghan, Bernard Mark (School of Architecture, Planning and Geomatics, 2020)
Having established that Constantia exhibits certain problems which are characteristic of the suburbanization of the urban fringe in general, it is necessary to consider how these problems could be resolved. In seeking such solutions, it is not only useful, but imperative, to determine sane framework of what the desired future state of the Valley should be and what role it should perform in the metropolitan context. In other words, what goals should be strived for and what objectives should be aimed at in order to facilitate the resolution of these goals. In establishing this framework, one returns to the basic underlying reasons for public sector intervention in the free market process - as outlined in Section 7.0 of Part One. This being "to regulate individual activity in the interests of the safety, health, morals and general well-being of the whole population" .